2023
DOI: 10.4236/ce.2023.143036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of COVID-19 on the Psychology of Saudi Technical College Students: Lessons and Tips

Abstract: During COVID-19 pandemic, many countries around the world considered a health control measures in order to face the significant spread of infection. But these considerations were accompanied by a disruption in the daily routines of many higher education students. Our research aimed to study the impact of the Corona epidemic on the psychological state of the behavior of vocational and technical training students in Saudi Arabia. The professional training program differs from the university program by its direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Secondly, our study's implications extend beyond academia and address broader mental health issues. Even post-pandemic, mental health remains a significant concern for higher education students (Denden & Alkhalifah, 2023;Radwan, 2022). Our research emphasizes the role instrumental support in online learning can play in enhancing student PsyCap, school satisfaction, and psychosocial well-being.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Secondly, our study's implications extend beyond academia and address broader mental health issues. Even post-pandemic, mental health remains a significant concern for higher education students (Denden & Alkhalifah, 2023;Radwan, 2022). Our research emphasizes the role instrumental support in online learning can play in enhancing student PsyCap, school satisfaction, and psychosocial well-being.…”
Section: Introductionmentioning
confidence: 90%
“…Factors contributing to these mental health issues can range from individual and interpersonal to institutional factors (Byrd & McKinney, 2012). The COVID-19 pandemic has exacerbated this problem and created a long-lasting negative impact on the mental well-being of post-secondary students (Chen & Lucock, 2022;Denden & Alkhalifah, 2023). For example, in a study of UK university students' mental health during the pandemic, Chen and Lucock (2022) found that over half reported high depression and anxiety that exceeded clinical thresholds.…”
Section: Introductionmentioning
confidence: 99%